Skrining Fitokimia dan Formulasi Sediaan Masker Gel Peel-Off Ekstrak Etanol Temulawak (Curcuma xanthorrhiza Roxb.) - Muslikh, Faisal; Aryantini, Dyah; Sari, Fita; Hesturini, Rosa Juwita; Winartiana, Winartiana; Prasetyawan, Fendy (Universitas Borneo Lestari, 2024)
Skin aging is a natural process influenced by intrinsic and extrinsic factors. This process often leads to various skin problems, including wrinkles, sagging, and hyperpigmentation. One of the main triggers of skin aging is oxidative stress, which produces reactive species oxygen (ROS) that can damage various components of the skin. Temulawak, locally known as Curcuma xanthorrhiza Roxb., has been traditionally used in Indonesia for various skin health conditions due to its antioxidant, antibacterial, and anti-aging properties. This research aims to create a new formula of peel-off gel mask from temulawak extract and evaluate the preparation. Two formulations were made, with the second formulation modified by adding the fragrance oleum rosae to reduce the aroma of temulawak. Evaluation was conducted through a series of tests, including The results showed differences between the two formulations, especially in the organoleptic test where Formula 2 experienced changes in color and aroma. However, other parameters were relatively similar between the two formulations. The developed peel-off gel mask has the potential to improve skin health, further research is needed to understand product acceptance by the public, using approaches such as hedonic testing. This will help in developing products that are more suitable for consumer needs and preferences.